Facilities Economics in Australia (Construction Economics and Building, 2012)
Facilities Economics in AustraliaAuthor: Bernard Williams with Brian PurdeyPublished by International Facilities & Property Information Ltd, forthcomingReviewed by Professor Craig Langston, Deakin University